Research and Practice on the Cultivation Mode of Civil Engineering Professionals in Characteristic Application-Oriented Colleges under the Background of Professional Certification - Rui Pan, Jixiang Liao, Shaonan Han, Dayong Wang, Jingbo Yu, Peifeng Cheng (Forest Chemicals Review)
The professional certification of engineering cultivation is a kind of specialized certification in the field of higher cultivation, which aims to improve the cultivation quality of engineering talents in colleges. Based on professional certification, this paper analyzes the problems existing in the cultivation of civil engineering majors in characteristic application-oriented colleges, and studies and optimizes the talent cultivation mode of civil engineering majors in characteristic application-oriented colleges. This paper puts forward the talent cultivation plan and core competence cultivation scheme of civil engineering specialty, studies the construction of cultivation staff, and puts forward the effective methods of cultivating students’ innovative consciousness. A cultivation quality monitoring and guarantee system is constructed to ensure that the cultivation of civil engineering majors in characteristic application-oriented colleges can meet the standards of engineering cultivation certification and meet the needs of national, social and industry development.